Effect of Bisphosphonates on Root Growth and on Chlorophyll Formation in Arabidopsis thaliana Seedlings - Manzano, Ana I.; Medina, F. Javier; Pérez-Zuñiga, Francisco J.; Sillero, Maria A. Günther; Sillero, Antonio (IntechOpen, 2012)
None